Damage-evoked signals in cochlear neurons and supporting cells - Wood, Megan Beers; Nowak, Nate; Fuchs, Paul Albert (Frontiers in Neurology, 2024)
In addition to hearing loss, damage to the cochlea can lead to gain of function pathologies such as hyperacusis. It has been proposed that painful hyperacusis, noxacusis, may be carried to the central nervous system by type II cochlear afferents, sparse, unmyelinated neurons that share morphological and neurochemical traits with nociceptive C-fibers of the somatic nervous system. Also like in skin, damage elicits spreading calcium waves within cochlear epithelia. These are mediated by extracellular ATP combined with IP3-driven release from intracellular calcium stores. Type II afferents are excited by ATP released from damaged epithelia. Thus, the genesis and propagation of epithelial calcium waves is central to cochlear pathology, and presumably hyperacusis. Damage-evoked signals in type II afferents and epithelial cells have been recorded in cochlear explants or semi-intact otic capsules. These efforts have included intracellular electrical recording, use of fluorescent calcium indicators, and visualization of an activity-dependent, intrinsic fluorescent signal. Of relevance to hyperacusis, prior noise-induced hearing loss leads to the generation of prolonged and repetitive activity in type II neurons and surrounding epithelia.